Discursive legitimation of human values: local-global power relations in global media discourse - Abduljalil Nasr Hazaea,; Noraini Ibrahim,; Nor Fariza Mohd Nor, (Penerbit UKM, 2014)
Construction of identities can be manifested in the form of competing legitimation discourses over an intercultural issue. This study investigates the power relations between local identities and global identities over the discursive legitimation of human values in global media discourse. Yemen Times (YT) is the most circulated English-language newspaper in Yemen. YT can be voice of Yemen to the world through the use of the English language and the online version of the paper. With the notion of English and globalization, the newspaper published discourses for maxims in the context of Improve Your English series produced by a non-local journalist. A maxim is extended in the form of an argumentative paragraph that contextualizes a single value. Employing an empirical research design, the study data were built of 152 maxims. As a theoretical and analytical approach, Fairclough's Critical Discourse Analysis (CDA) is concerned with globalization, discourse, power and ideology. The study adopts these concepts to show how the processes of globalization are ideological choices that serve the interest of global agency. After identifying human values through thematic analysis, a three-dimension analysis of discourse was used to reveal the competing legitimation discourses. Clause complex was used as the unit of analysis where the focus was on the social actors of the projecting clauses. The discourse analysis reveals that local identities were suppressed or backgrounded in the texts. Global identities dominated the texts in the form of global literary discourse, global political discourse, global religious discourse, global philosophical discourse and global anonymous discourse. The exclusion of local identities shows that human values were employed in intercultural communication to serve the interest of global hegemony.